ORGANIZE SELF-DEPENDENT COGNITIVE ACTIVITY OF PUPILS ON PHYSICS USING INFORMATION TECHNOLOGIES - Shаrko, В.Д. (Journal of Information Technologies in Education (ITE), 2012)
This article discusses the possibility of training teachers of physics to development of students' cognitive independence means of information technology.